1986
DOI: 10.1007/bf01658148
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic resection for hepatocellular carcinoma associated with liver cirrhosis

Abstract: Sixty‐three patients with hepatocellular carcinoma associated with cirrhosis received various kinds of treatment at our clinic during the past 21 years. Of these, 35 patients who underwent hepatic resection were divided into a large tumor group (tumors more than 5 cm in diameter) and a small tumor group (tumors less than 5 cm in diameter), and the operative results of both groups were studied. There was a difference in the average ages between the 2 groups (p <0.05), but there was no difference in the duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 13 publications
(21 reference statements)
1
22
0
1
Order By: Relevance
“…These rates are comparable to results in other Asian and Western studies. 5,20 Similarly, in both Western and Asian series, AFP positivity has been shown to be an independent risk factor for poor prognosis by multivariate analysis. 20,21 Advanced age as an adverse prognostic factor has been demonstrated in some studies 22 but not in others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These rates are comparable to results in other Asian and Western studies. 5,20 Similarly, in both Western and Asian series, AFP positivity has been shown to be an independent risk factor for poor prognosis by multivariate analysis. 20,21 Advanced age as an adverse prognostic factor has been demonstrated in some studies 22 but not in others.…”
Section: Discussionmentioning
confidence: 99%
“…Even after successful resection, there is a 50% recurrence rate 3 and overall survival hovers between 20-40% in various series. 4,5 In southeast Asia and sub-Saharan Africa, HCC is a prevalent cause of cancer death. Hepatitis B and C viruses and aflatoxin exposure have been identified as risk factors in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…A positive association of cirrhosis of the liver in 80-90% of patients with HCC has been demonstrated in reports from Northern regions. [12][13][14][15][16][17] Oka et al 1990 18 found the yearly incidence rate of HCC in cirrhotics varies from 3% in the West 19 to as high as 11% in Japan. Tsukuma et al1990 8 in a prospective study from Japan reported liver cirrhosis and viral hepatitis as risk factors for HCC, each carrying a 3-year cumulative risk of 12.5 and 3.8%, respectively.…”
Section: What Are the Risk Factors For Hepatocellular Carcinoma In Inmentioning
confidence: 99%
“…Unlike the normal liver, which, within [3][4][5][6][7][8][9][10][11][12] months can regenerate to its original size and function, even after 80% resection, the cirrhotic liver has impaired regenerative ability. Indeed, until recently, the cirrhotic liver was thought to be unable to regenerate [7].…”
Section: Impaired Regenerationmentioning
confidence: 99%
“…Conversely, 10-20% of patients with cirrhosis from any etiology, will go on to develop HCC [3,6]. Thus, the majority of patients who require resection also have cirrhosis or impaired liver function.…”
Section: Introductionmentioning
confidence: 99%